B-Type Natriuretic Peptide as a Predictor of Short-Term Mortality in On-Pump Coronary Artery Bypass Grafting - Jamil Alli Murad Junior; Maurício Nassau Machado; Marcio Pimentel Fernandes; Marcelo José Ferreira Soares; Ingrid Helen Grigolo; Cristiane Carvalho Singulane; Moacir Fernandes de Godoy (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: The present study refers to a determination of the preoperative B-type natriuretic peptide is a predictor of short-term all-cause mortality in patients undergoing on-pump coronary artery bypass graft surgeries. Methods: Two hundred and twenty-one patients undergoing on-pump coronary artery bypass graft surgeries were evaluated prospectively during a 30-day postoperative follow-up period. Serum B-type natriuretic peptide concentration was measured without a 24-hour period prior to the surgical procedure and the value obtained was correlated with a short-term all-cause mortality. Results: Data analysis showed that all-cause mortality rates were equal to 9.5% in 30 days. Accuracy analysis by the receiver operating characteristic curve found an ideal cut-off value of B-type natriuretic peptide equal to 150 pg/mL in relation to mortality (AUC=0.82, 95% CI=0.71-0.87, P<0.001). Multivariate analysis showed that B-type natriuretic peptide value greater than or equal to 150 pg/mL (P=0.030, HR=3.99, 95% CI=1.14-13.98) was an independent predictor of all-cause mortality in a 30-day follow-up period. Conclusion: Preoperative serum B-type natriuretic peptide concentration is an independent predictor of short-term all-cause mortality in patients undergoing coronary artery bypass grafting with cardiopulmonary bypass.